PHYSICAL MODELING OF THE COMBINATION OF BAMBOO POLE BREAKWATER AND GREEN MUSSELS CULTIVATION FOR THE EFFECTIVENESS OF NATURAL COASTAL PROTECTION SYSTEMS - Ode Faiz Bil Iman, La
Indonesia is one of the maritime countries in the world with a water area of 3.25 million km2 or around 63% of Indonesia's territory and also has a coastline of 81,000 km. This causes coastal areas in Indonesia to be vulnerable to several problems such as coastal erosion. Beach erosion is a major problem in coastal areas. Beach erosion often occurs in Indonesia's coastal areas. Natural coastal protection using vegetation such as mangroves is found in many places in the world, including in Indonesia. Mangroves are very effective in protecting beaches from coastal erosion. However, protecting the coast with mangrove plants requires quite a long time for the mangrove plants to grow and develop. So protection is needed for young mangroves. To solve this problem, a natural coastal protection system combining the main natural coastal protection and man-made temporary structures is proposed. The temporary man-made structure used in this research is a bamboo pole breakwater. Apart from protecting mangroves from waves, bamboo pole breakwaters can be used as a medium for cultivating green mussels. This research aims to determine the effect of model thickness (diameter) and roughness on the physical model of a combination of bamboo pole breakwaters and green mussels in reducing wave height and determine the most appropriate type of bamboo pole breakwater model. Laboratory experiments are carried out on 2D wave channels. There are 11 wave conditions used during laboratory testing. This research focuses on the wave transmission coefficient parameters that pass through the coastal protection system in determining the most effective combination configuration of bamboo pole breakwaters to reduce wave height so as to reduce coastal erosion. The research results show that the combination model of bamboo pole breakwater and green mussels can increase the wave reduction percentage by 2.54%. Based on the results of physical modeling, the most effective combination of bamboo pole breakwaters is the one with the tightest distance between columns and rows of bamboo poles with a thickness (diameter) of the bamboo pole and green mussels models of 2.40 cm and a roughness of 0.33 cm.